Model of shared decision-making in medical practice - Naumenko Галина (Psychosomatic Medicine and General Practice, 2019)
Today, the issue of patient-oriented delivery of medical services is particularly acute. This is not just about the good manners of doctors: polite smile, greetings, address to the patient with respect, as well as medical results due to the expressed professional competencies. The quality of communication in the medical sector plays a huge role in the provision of qualified medical care, due to the fact that it promotes: more effective interviewing or collecting information (accuracy, productivity, support for the patient); increasing the satisfaction of both the patient and the specialist; improvement of the patient’s health, adherence to the prescribed therapy (compliance). Thus, in order for biomedical technologies to be safe and effective, they should be used on the basis of effective communication and attitudes. One of the effective methods of a patients-physician interaction is the method of shared decision-making (SDM). This is a process in which patients are encouraged to participate in choosing appropriate treatment or self-management options. The model has three stages: implementation of the choice; description of options; assist patients in learning benefits and decision making. SDM is appropriate when there is more than one reasonable course of action, and no option is evidently not the best for all. In these cases, it has been proved that the formation of a patient’s attitude to possible benefits and risks of the treatment of the disease should be a key factor in decision-making. When there is a common view, doctors can better use motivational approaches to promote behavioral change, overcome clinical inertia, and promote self-regulation and community management by patients throughout the treatment and rehabilitation process.